1993
DOI: 10.3109/09638289309165865
|View full text |Cite
|
Sign up to set email alerts
|

Job perspectives in facioscapulohumeral muscular dystrophy

Abstract: The working career of 138 adult patients with autosomal dominant facioscapulohumeral muscular dystrophy (FSHD) was studied using a mailing questionnaire. Of 126 patients with an occupational history, the average female and male working career was 15 to 30 years, respectively. Of 61 respondents actually holding a job, only nine had adjustments for disease-related handicaps. Reaching above and below shoulder level was required in 24 jobs, although shoulder weakness is a presenting symptom of FSHD. In spite of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 6 publications
2
29
1
Order By: Relevance
“…TNO Arbeid validated their questionnaire in several research projects and reported good reliability of the test. 6,7 The employment situation was assessed both preinjury and after reintegration. Respondents were asked to report the changes in type of job and working hours, vocational retraining, job modifications, contacts with work professionals, income and their opinion on the working conditions and social atmosphere.…”
Section: Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…TNO Arbeid validated their questionnaire in several research projects and reported good reliability of the test. 6,7 The employment situation was assessed both preinjury and after reintegration. Respondents were asked to report the changes in type of job and working hours, vocational retraining, job modifications, contacts with work professionals, income and their opinion on the working conditions and social atmosphere.…”
Section: Questionnairementioning
confidence: 99%
“…Respondents were asked to report the changes in type of job and working hours, vocational retraining, job modifications, contacts with work professionals, income and their opinion on the working conditions and social atmosphere. The TNO assessment includes an educational level scale (score [1][2][3][4][5][6][7][8]. Changes in the type of hobbies and sports were also assessed, as was the support of the rehabilitation team in developing new leisure activities.…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…TNO Arbeid validated their questionnaire in several research projects. 4,5 Data became available on the employment situation both preinjury and after the reintegration including having a job, the type of job, the job contract and number of working hours (appendix). Respondents were asked to report their income, educational level (grades 1-8), vocational retraining, job adjustments and contacts with reintegration professionals.…”
Section: Questionnairementioning
confidence: 99%
“…However, several studies have shown that reintegration interventions do not enable all people with chronic diseases and disabilities to resume work. [4][5][6][7] The purpose of this study was to extend our knowledge about the process and the outcomes of reintegration in paid work following a SCI.…”
Section: Introductionmentioning
confidence: 99%